ANALISIS FAKTOR YANG MEMPENGARUHI KECEMASAN PADA IBU HAMIL TERHADAP HUBUNGAN SEKSUAL DI RSIA KHADIJAH 1 MAKASSAR - Nelcy, Yuliana; Vitayani, Sri; Abbas, Hasriwiyani Habo (Window of Health : Jurnal Kesehatan, 2019)
Sexual relations are a primary need for married couples. However, many couples who disagree about sex during pregnancy are caused by anxiety from each partner. The general purpose of this research is to analyze the factors that influence anxiety in pregnant women against sexual relations in RSIA Sitti Khadijah 1 Makassar City.This research approach is observational, with a cross sectional approach. The population in this study were all pregnant women in RSIA Sitti Khadijah 1, Makassar City. The sample in this study was conducted by accidental sampling.The results showed the majority of respondents had the age in the risk category as many as 65.7%. The results of statistical tests obtained X2 count (7.672)> X table (5.991) and the value of p value = 0.024 <value of Î± = 0.05, most respondents have gestational age in the risk category as many as 53.7%. The results of statistical tests obtained X2 count (13,449)> X table (5,991) and p value = 0,001 <value Î± = 0,05, most respondents have parity in the risk category as many as 58,2%. Statistical test results obtained X2 count (9.217)> X table (5.991) and p value = 0.007 <value Î± = 0.05, most respondents have economic status in the category <UMK as many as 50.7%. The results of statistical tests obtained X2 count (8.941)> X table (5.991) and the value of p value = 0.009 <value of Î± = 0.05, most of the respondents did not work as many as 55.2%. Statistical test results obtained compute X2 (7,783)> X table (5,991) and p value = 0,019 <value Î± = 0,05, most respondents have education in the low category as many as 59,7%. The results of statistical tests obtained X2 count (4.353) <X table (5.991) and the value of p value = 0.117> the value of Î± = 0.05, the variables that most influence the anxiety in pregnant women on sexual relations are socio-economic.It is expected that health workers can be included in KIE (Information and Education Communication) regarding sexual activity so that it is expected that all pregnant women who have their pregnancies will not experience anxiety.Keywords: Age, Age of Pregnancy, Parity, Socio-Economic, Job, Education, Anxiety, Sexual RelationshipBibliography: 50 (1990 - 2017)